PERBEDAAN PERSEPSI MAHASISWA MENGENAI RISIKO PROFESI JURNALIS SEBELUM DAN SESUDAH MENONTON FILM DOKUMENTER KUBUR KABAR KABUR - Adinda Ristiandini, Raisya; Gumilar, Gumgum; Sri Mulyani, Henny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing number of violence cases against journalists in Indonesia indicates that the journalism profession involves substantial occupational risks, which are not always fully understood by journalism students. This study aimed to examine differences in students’ perceptions of the risks of the journalism profession before and after watching the documentary film Kubur Kabar Kabur based on the Stimulus-Organism-Response (SOR) theory. This research employed a quantitative approach using a one-group pretest-posttest experimental design. The population consisted of journalism students in Greater Bandung, with 162 respondents selected through proportionate stratified random sampling. Data were analyzed using the Wilcoxon Signed Rank Test and N-Gain Score analysis. The results showed significant differences in students’ perceptions before and after watching the documentary film, as indicated by a Z value of -10.635 and a significance value of p < 0.001. In addition, the N-Gain score of 44.62 indicated a moderate level. The findings suggest that the documentary film successfully enhanced students’ cognitive, affective, and conative perceptions regarding the risks of the journalism profession. Therefore, documentary films can be utilized as educational media to improve students’ understanding of occupational risks in journalism.